Experimental and numerical investigation on hyperelastic sealing disc contact behavior in pipeline, a comparison between fluid-driven and pull-through approaches - Salar Jouzani; Mohammad Hossein Soorgee (Journal of Pipeline Science and Engineering, 2025)
Pipelines are widely recognized as the safest and most efficient means of fluid transportation. Pipeline pigging, a secure and reliable technique, is employed for both cleaning and sealing pipelines to optimize efficiency. Since pigging operation requires differential pressure (Δp) to facilitate pig movement, this pressure must correspond to the pipeline’s operational conditions. Consequently, studying the required Δp for sealing discs, which serve as primary sealing elements of pigs, is crucial. The primary focus of this study is to examine the difference between pulling the pig using a cable and propelling it with fluid. Furthermore, the main novelty of this research is to experimentally investigate a single sealing disc and conduct fluid-driven tests on it. To study more precisely, three sealing discs with various thicknesses and the same hardness have been launched into a 6-inch spool test, containing five pipes with different wall thicknesses, resulting in multiple oversize ratios (%Osz). In the experimental study, both fluid-driven and pull-through tests were conducted. The range of discrepancy between two methods varies from 15% to 26% for different oversize ratios which is considerable. Additionally, A 2-D axisymmetric nonlinear numerical simulation was conducted in a finite element software ABAQUS in order to study the behavior of sealing discs. Using a pressure-dependent friction coefficient with the proper hyperelastic model was key to achieving simulations that have good agreements with experimental results, with discrepancy of less than 10% in all extracted pressures.